2016
DOI: 10.1111/pde.13032
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Hemangioma Severity Scale as a Triage Tool and Predictor of Need for Treatment

Abstract: The HSS may be a useful tool for primary care physicians in identifying high-risk IHs that may benefit from therapy. This easy-to-use scale can improve clinical outcomes by identifying which patients need intervention to minimize complications. IHs with total HSS scores of 6 or greater should be referred for subspecialty evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…Furthermore, the study was performed in a reference centre where severe IHs were more likely to be referred. Nevertheless, our cohort seems to be comparable with other studies in terms of percentages of those treated for IHs (~10%), gender ratio (most were female), predominant location being on the head (nearly 80%), date of onset, predominant clinical subtype and indications for OP …”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, the study was performed in a reference centre where severe IHs were more likely to be referred. Nevertheless, our cohort seems to be comparable with other studies in terms of percentages of those treated for IHs (~10%), gender ratio (most were female), predominant location being on the head (nearly 80%), date of onset, predominant clinical subtype and indications for OP …”
Section: Discussionsupporting
confidence: 85%
“…15 Furthermore, although the HSS was used to assist IH treatment decisions or referral, the cutoff values used for decision-making were inconsistent. 16,17 The current study had some limitations. One of the constraints of conducting a real-world observational study was that the representativeness of the participating physicians was potentially limited, restricting generalizability.…”
Section: Figurementioning
confidence: 93%
“…Step 2: Completion of the IHReS questionnaire Open access study also revealed the cut-off values of IHs with total HSS scores of 6 or greater should be referred for subspecialty evaluation. 15 As a triage purpose, the HSS may be a useful tool for primary care physicians in identifying high-risk IHs that may benefit from therapy. The HSS is a one-page scale with scoring items that require thorough information to complete the total score.…”
Section: Discussionmentioning
confidence: 99%